Insulin Detemir Causes Lesser Weight Gain in Comparison to Insulin Glargine: Role on Hypothalamic NPY and Galanin. (13th August 2014) - Zafar, Mohammad Ishraq; Hu, Cuining; Liu, Danfeng; Shafqat, Raja Adeel; Gao, Feng
Abstract : Objective. Compared with other insulin analogues, insulin detemir induces less weight gain. This study investigated whether this effect was achieved by influencing the hypothalamic appetite regulators neuropeptide Y (NPY) and galanin (GAL). Methods. Type  2 diabetic rat models were established with a high-fat diet and intraperitoneal injection of STZ. All rats were divided into NC, DM, DM+DE and DM+GLA groups. Glycemic levels of all study groups were checked at study onset and after 4 weeks of insulin treatment. Food intake and body weight were monitored during treatment. After 4 weeks, the hypothalamus of rats was examined for NPY and GAL mRNA and protein expression. Results. After 4 weeks of treatment, compared with the DM+GLA group, the DM+DE group exhibited less food intake ( P < 0.05 ) and less weight gain ( P < 0.05 ), but showed similar glycemic control. The expression of hypothalamic NPY and GAL at both mRNA and protein level were significantly lower ( P < 0.05 ) in the DM+DE group. Conclusion . Insulin detemir decreased food intake in type 2 diabetic rats, which led to reduced weight gain when compared to insulin glargine treatment. This effect is likely due to downregulation of hypothalamic NPY and GAL.